Derdestlik, Dava Açma Süresinin Aşmama ve İşkence İddialarında Asgari Bir Acı Eşiğinin Aşılması Açısından Ali Deniz Kutluk ve Diğerleri Türkiye Kabul Edilmezlik - Tezcan, Durmuş (Seçkin Yayıncılık, 2014)
Ali Deniz Kutluk and Others v. Turkey – Inadmissibility Decision of ECtHR Regarding the Claims of Being Pending, Not Exceeding the Time Limit of Filing a Lawsuit and Torture in the Situation of Exceeding Minimum Threshold of Pain. The decision is important to underline the some basic principles, which are accepted in the ECtHR Judgment. At the same judgment named as Balyoz, the applicants were examined under a trial because of the similarity. The subject of the case is based of a claim of attempt to plan a military coup d’etat by criminal organization which is formed by the military personnals.
Keywords: Ali Deniz Kutluk ve diğerleri kararı